Antibiotic resistance and class 1 integron gene dynamics along effluent, reclaimed wastewater irrigated soil, crop continua: elucidating potential risks and ecological constraints. (1st November 2019) - Marano, Roberto B.M.; Zolti, Avihai; Jurkevitch, Edouard; Cytryn, Eddie
Abstract: Reuse of municipal wastewater is a growing global trend, but currently there is lack of consensus regarding the potential dissemination of antibiotic resistance elements by treated wastewater irrigation. We tracked intI 1, a proxy for anthropogenic pollution, and an assemblage of antibiotic resistance genes associated with mobile elements and/or wastewater ( bla GES, bla OXA2, bla OXA10, bla TEM, bla CTX-M-32 and qnr S) in treated wastewater effluents, effluent stabilization reservoirs, and along irrigation water-soil-crop continua in experimental lysimeters and large-scale commercial fields. While several of the targeted antibiotic resistance genes were profuse in effluents, there was almost no correlation between gene abundance in irrigation water and those detected in soil, and no evidence of systematic gene transfer to irrigated soil or crops. In contrast, soil intI 1 abundance correlated strongly to irrigation water levels in lysimeters and sandy field soils, but this was not the case for clay-rich soils or for most of the analyzed crops, suggesting that intI 1 may not always be a reliable marker for tracking the impact of treated wastewater irrigation. We hypothesize that "ecological boundaries" expedited by biotic and abiotic factors constrain dissemination of antibiotic resistance elements, and assert that a more holistic perception of these factors is crucial for understanding and managing antibiotic resistance dissemination. Graphical abstract: Image 1 Highlights: We targeted antibiotic resistance genes (ARGs) in effluents and irrigated fields. bla OXA and bla GES genes were strongly linked to treated wastewater effluents. Effluent storage in reservoirs substantially reduced ARG abundance. intI 1 distribution in irrigated soil was only partially linked to water quality. Ecological barriers seem to restrict ARG dissemination to irrigated soil and crops.